2020
DOI: 10.1002/app.49621
|View full text |Cite
|
Sign up to set email alerts
|

Halloysite nanotubes immobilized by chitosan/tannic acid complex as a green flame retardant for bamboo fiber/poly(lactic acid) composites

Abstract: In order to develop an environmentally benign flame retardant for bamboo/ PLA composites (BPC), chitosan (CS) and tannic acid (TA) were used as cationic and anionic polyelectrolyte respectively to stabilize halloysite nanotubes (HNT) on the surface of bamboo fiber (BF) and poly(lactic acid) (PLA). Mechanical performance tests showed that the flexural properties of BPC were moderately enhanced with the addition of HNT, while the incorporation of CS/TA complex (FR) exhibited a slight increase. The results of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 51 publications
(60 reference statements)
1
9
0
Order By: Relevance
“…This could be explained by the entrapment of char residue in a polymeric structure, which retarded the diffusion of volatile degradation materials out from the sample, consequently decelerated the materials' decomposition, leaving in higher weight percentage. The result was in accordance with the study conducted by Jin et al, 59 who observed the enhancement in thermal stability and greater char formation through the simultaneous Cs and TA addition into PLA/bamboo fiber composite.…”
Section: Thermogravimetric Analysissupporting
confidence: 92%
“…This could be explained by the entrapment of char residue in a polymeric structure, which retarded the diffusion of volatile degradation materials out from the sample, consequently decelerated the materials' decomposition, leaving in higher weight percentage. The result was in accordance with the study conducted by Jin et al, 59 who observed the enhancement in thermal stability and greater char formation through the simultaneous Cs and TA addition into PLA/bamboo fiber composite.…”
Section: Thermogravimetric Analysissupporting
confidence: 92%
“…2 wt% TA-MoS2/PAN [36] 2.9 332.8 N/A N/A 12.1 N/A N/A BPC/5FR@5HNT [37] 30.8 723.0 N/A N/A 136.6 N/A N/A PU-TA@RG05 [38] N/A 235.23 ± 3.78 N/A N/A 21.72 ± 0.42 N/A N/A P5/T2/S [32] 7 166 37 4.5 7.5 N/A N/A systems. However, when compared to one another, no one system completely outperforms our TA composites, with few even getting close.…”
Section: Quantitative Flammability Resultsmentioning
confidence: 99%
“…Chitosan/tannic acid coatings applied on biocomposites fillers increase the fire resistance of biocomposites. This kind of coatings has a potential application in materials engineering [ 275 ].…”
Section: Tannic Acidmentioning
confidence: 99%